Quorum Sensing Activity in Pandoraea pnomenusa RB38 - Robson Ee (Sensors, 2014)
Strain RB38 was recovered from a former dumping area in Malaysia. MALDI-TOF mass spectrometry and genomic analysis identified strain RB-38 as Pandoraea pnomenusa. Various biosensors confirmed its quorum sensing properties. High resolution triple quadrupole liquid chromatography–mass spectrometry analysis was subsequently used to characterize the N-acyl homoserine lactone production profile of P. pnomenusa strain RB38, which validated that this isolate produced N-octanoyl homoserine lactone as a quorum sensing molecule. This is the first report of the production of N-octanoyl homoserine lactone by P. pnomenusa strain RB38.